ANALISIS PENGARUH TINGKAT SUKU BUNGA, NON PERFORMING LOAN, DAN LOAN DEPOSIT RATIO TERHADAP PENYALURAN KREDIT UMKM Studi Kasus Bank Umum di Indonesia Periode 2008-2017 - Aldhella Arcy Desya; Lorentino Togar Laut; Yustirania Septiani (DINAMIC : Directory Journal of Economic, 2019)
The purpose of this study was to determine how much influence the variable amount of interest rate, non performing loan and loan deposit ratio either simultaneous or partially affect the variable SME’s lending. The data collected is secondary data obtained from commercial banks performance  report    year  2008-2017.  Data  collection  technique  obtained  from  Indonesian banking  statistics  for  15  years  from  the  Bank  Indonesia.  In  this  study  using  α  of  5% and techniques of multiple linear regression data analysis, statistical tests, and classical assumption. The survey results revealed detachment from the classical assumption, then the estimation results of  regression  and  t  test  showed  that  the  interest  rate  during  the  year  2008-2017  have  no significant effect on SME’s lending. However, t test of non performing loan and loan deposit ratio during the year 2080-2017 showed a significant effect SME’s lending. simultaneously shows that the interest rate, non permorming loan and loan deposit ratio have a significant effect on SME’s lending. Keywords: interest rate, non performing loan, and SME’s lending